Quality management in nursing assistance at clinical surgery unit - Liange Arrua Rabenschlag; Suzinara Beatriz Soares de Lima; Thaís Dresch Eberhardt; Marciane Kessler; Rhea Silvia de Avila Soares; Silviamar Camponogara (Universidade Federal de Santa Maria, 2015)
Aim: to identify the facilities and difficulties that nurses encounter in management of quality in nursing assistance at clinical surgery unit. Method: descriptive and qualitative research performed at a University Hospital in South Brazil, from July to September 2013. Semi-structured interviews were conducted and evaluated according to Minayo thematic analysis. Results: two thematic categories were emerged: facilities in quality management at clinical surgery unit, composed by the topics professional experience, interaction with teamwork and integration with the workplace; and difficulties in quality management at clinical surgery unit through themes that pointed to work overload, the insufficient number of nursing staff, physical structure and insufficiency of material resources. Conclusion: the study will contribute with the nurses, because identifies facilitating and hindering factors in management of quality in nursing assistance, enabling strategies in search for effective care and health excellence